Sexual Function and Sexual Behavior in Women with Breast Cancer Having Sexual Distress, Zanjan, Iran - Esmkhani M; Kharaghani R; Merghaty Khoie E; Faghihzadeh S; Shakibazadeh E (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Sexual relationships of women with breast cancer are affected by diagnostic and therapeutic procedures. Objectives: The aim of this study was to assess sexual function and sexual behavior in women with breast cancer having sexual distress in Zanjan in 2015-2016. Methods: This cross sectional study was part of a larger study, which was performed on 75 women with breast cancer in the oncology clinic of Valiasr hospital and Mehraneh charity clinic. Sampling was based on a purposeful approach. Data were collected using a demographic questionnaire, Sexual Function Questionnaire (FSFI), and indigenous sexual behavior questionnaire in women of reproductive age (SBQ). Data were analyzed using the Chi-squared and Spearman-Pearson tests. Results: A majority of the women (77.3%) had an undesirable sexual function and orgasm dysfunction (65.3%). Besides, it was found that the majority of women had low to moderate sexual behavior. The correlational analyses related to sexual function and sexual behavior and their sub-scales showed that there was only a significant positive relationship between the sexual capacity subscale and the total sexual function scale (P<0.005). Conclusion: Women with breast cancer had sexual dysfunction and behavior. Designing and implementing related counseling programs may help to reduce sexual distress, improve sexual function and marital satisfaction, and enhance the quality of life of affected women.